PENENTUAN KADAR ZAKAT PERTANIANDAN RELEVANSINYA TERHADAP PERTANIAN MASYARAKAT INDUSTRI DI INDONESIA - Saifuddin; Dewi Fatimah (Fakultas Syariah IAIN Kediri, 2023)
Ratio of agriculture zakat is 1.400 kg grain or 653 kg rice, whereas the quantity of zakat is 5 % if the irrigation needs cost and 10 % if not. If we compare with trade zakat, the ratio of it is higher than of agriculture, but the quantity of trade zakat is only 2,5%. The reason is because Madinah, city of Messanger, is an agrarian city where the main profession is farmer. The trader is the secondary one. It is different with Macca, the main profession of its people is trading. The problem arises now is when it is contextualized with Indonesian agriculture which is eliminated. Absolutely, it is not fair. This article will discuss that problem. From the results of the analysis it can be concluded that agriculture in Indonesia has a different variety. It is already irrelevant the level of agricultural zakat when compared to the beginning of the lowering of the agricultural zakat order. Because in Indonesia itself agriculture is not like the old days. If the harvest does not reach the nisab, then no zakat is required. As for industrial-based agriculture, it depends on the type. If it is included in agribusiness, the zakat issued is trade zakat, which is 2.5% with haul according to trade zakat